2007
DOI: 10.1016/j.ejpain.2006.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dorsal root ganglion CGRP expression in a chronic inflammatory model of the rat knee joint: Differential modulation by rofecoxib and paracetamol

Abstract: Neuropeptide-expressing small diameter sensory neurones are thought to be vital in generating inflammatory hyperalgesic responses. Within the dorsal root ganglion (DRG), both the levels of the neuropeptide calcitonin gene-related peptide (CGRP) and the numbers of CGRP-immunoreactive (CGRP-IR) DRG neurones have been shown to increase in a number of acute adjuvant-induced inflammatory pain models. The aim of this study was to look specifically at changes in numbers of CGRP-IR DRG neurones in a chronic model of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
(59 reference statements)
6
31
0
Order By: Relevance
“…Osteoarthritic conditions activate the nociceptive system, and CGRP is elevated in the DRGs [25,34] . A decrease in the number of CGRP-positive DRG neurons was also consistent with improved pain behavior [25,35] . In accordance with a previous study, our data show that the percentage of CGRP-positive neurons was markedly increased at advanced stages in the MMT model, whereas ZOL treatment initiated at early stages reduced the expression of CGRP.…”
Section: Discussionmentioning
confidence: 59%
“…Osteoarthritic conditions activate the nociceptive system, and CGRP is elevated in the DRGs [25,34] . A decrease in the number of CGRP-positive DRG neurons was also consistent with improved pain behavior [25,35] . In accordance with a previous study, our data show that the percentage of CGRP-positive neurons was markedly increased at advanced stages in the MMT model, whereas ZOL treatment initiated at early stages reduced the expression of CGRP.…”
Section: Discussionmentioning
confidence: 59%
“…Additionally, ketoprofen-treated rats showed higher CGRP expression, particularly in the 4d MA+2d Ket group. Staton et al [48] observed decreased CGRP expression following oral administration of rofecoxib to CFA knee-injected rats between days 13 and 17. Separated quantification of small-or medium-sized cells, but particularly the differing treatments (ways of administration and timepoints) may account for the disagreement with our data in MA.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, changes in CGRP expression within the dorsal root ganglion (DRG) have been studied in various pain models. The number of CGRP-immunoreactive (CGRP-IR) DRG neurons increased or decreased in inflammatory and neuropathic pain models [11,14,21]. In these studies, phenotypic changes in DRG CGRP expression have included both a change in the number of CGRP-IR neurons and a switch to CGRP expression in small or large DRG neurons.…”
mentioning
confidence: 99%